Alterações na expressão do Hormônio Concentrador de Melanina (MCH) na área hipotalâmica lateral do rato ao longo do desenvolvimento pós-natal e envelhecimento - Machado, Carla de Moraes [UNESP] (2015)
The Melanin-Concentrating Hormone (MCH) is a nonadecapeptide located mainly in neurons in the lateral hypothalamic area (LHA), which innervate several regions of neuraxis. MCH is involved in many functions as reproduction, aspects of motived behaviors, motor activity, sensorial information, temperature control, memory, learning, anxiety, sleep-wake cycle and feeding behavior in which the MCH plays an orexigenic role. The energy consumption in aging is reduced as well as, the expression of MCH presents alterations associated with age. Therefore, we analyzed the variations in the expression of MCH at different ages in the lateral hypothalamic area, using stereology (to estimate the number of MCH-ir neurons, area, volume and neuronal density), 3D reconstruction (to study the distribution of MCH-ir neurons) and optical density after in situ hybridization protocol for ppMCH RNAm (to measure the hibridizated area, the mean optical density and the integrated optical density [IOD]) in the LHA and its three regions. In this study, 35 animals were divided in 7 experimental groups of 14 (neonate), 28 (prepubescent), 50 (pubescent), 90 (young adult), 210 (middle aged adult), 540 (senescent adult) and 750 (elderly adult) postnatal days. All the animals were perfused via the ascending aorta, the brains were collected and processed by immunohistochemistry and in situ hybridization protocols to analyze the expression of MCH in the lateral hypothalamic area. LHA neurons number increased only between groups of 14 and 28 days, and its area and volume significantly smaller in 14-days group when in respect to all other groups but the 750-days one. However, there weren't differences in neuronal density among groups. MCH-ir neurons distribution in LHA and contiguous regions was similar among all groups as well. Hypothalamic MCH-ir neurons has shown uniform rates in and out of LHA, but after analyzing its distribution in mamillary, tuberal and anterior ...